(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper examines the influence of modern agricultural technology with special focus on resettled Jenukuruba community. The Jenukuruba Community are concentrated in the districts of Mysore and Chamarajanagara bordering the states of Tamil Nadu, Kerala and Karnataka. Habitually Jenukuruba Community are traditional honey collectors by profession. The Jenukuruba Community have been evicted from forests in the name of Tiger Reserves in Nagara Hole & Bandipur. Some of them have been repositioned outside the forest boundaries. The Jenukuruba Community have fought against the Government of Karnataka Forest Law, for their traditional rights over land and forest resources, but they are denied access to forests main land, and forest resources as they did earlier. Their unfailing demand for share of land in reserved forests Under the Forest Rights Act has become fruitless. Government of Karnataka has supported the Jenukuruba community resettlement with cultivable and arable land in nearby area. But, young Jenukuruba community farmers are far behind in utilizing the mechanization techniques. Technology in agriculture affects many areas of agriculture along with farm mechanization; farmers will be able to achieve self sufficiency in food grain production by employing chemical fertilizers, pesticides, Hi- breed seeds and improved irrigation methods. With the advent of digital technology the scope for mechanized agriculture has become more rewarding.